Ant Colony Optimization Modelling for Task Allocation in Multi-Agent System for Multi-Target - Iis Rodiah; Medria Kusuma Dewi Hardhienata; Agus Buono; Karlisa Priandana (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2022)
Task allocation in multi-agent system can be defined as a problem of allocating a number of agents to the task. One of the problems in task allocation is to optimize the allocation of heterogeneous agents when there are multiple tasks which require several capabilities. To solve that problem, this research aims to modify the Ant Colony Optimization (ACO) algorithm so that the algorithm can be employed for solving task allocation problems with multiple tasks. In this research, we optimize the performance of the algorithm by minimizing the task completion cost as well as the number of overlapping agents. We also maximize the overall system capabilities in order to increase efficiency. Simulation results show that the modified ACO algorithm has significantly decreased overall task completion cost as well as the overlapping agents factor compared to the benchmark algorithm.